Criminal Law Analysis of the Case of a Mother who Killed Her Two Children and Committed Suicide in Bandung - Bayu Suryo Aji; Suparji Suparji (STAINI Press, 2026)
The phenomenon of filicide defined as the killing of a child by a parent—has once again drawn public attention following a case involving a housewife in Bandung Regency who allegedly poisoned her two children before committing suicide. This article examines the incident from the perspective of Indonesian positive criminal law. First, the perpetrator’s actions may normatively be qualified under Article 338 of the Indonesian Criminal Code (KUHP) concerning murder, or Article 340 if premeditation is established, for instance through the purchase of poison and the preparation of a suicide note. Second, there is potential for the application of Article 44 of the KUHP if the investigation reveals that the perpetrator suffered from severe depression or a mental disorder that eliminated criminal responsibility. Third, the study highlights the limitations of criminal law when the perpetrator has died, in accordance with the principle actio personalis moritur cum persona, whereby criminal liability ceases upon the death of the individual. Consequently, law enforcement efforts no longer focus on punishment, but rather on establishing legal facts, investigating the possibility of accomplices, and ensuring the protection of children's rights. The findings of this study underscore that in cases of filicide-suicide, Indonesian positive criminal law encounters a normative dilemma: while the act of murder may be formally established, criminal liability is extinguished due to the perpetrator’s death. This condition shifts the function of investigation from merely prosecuting the offender to uncovering motives, ensuring the absence of complicity, and serving as a basis for policy recommendations on prevention. From an academic perspective, this research demonstrates the importance of integrating criminal law with criminological and mental health approaches, particularly in formulating strategies for the protection of vulnerable families and the prevention of similar crimes in the future.